Impacto de uma formulação comercial de herbicida à base de glifosato sobre girinos de Boana faber em condições controladas de laboratório - Hentges, Cristiano Roberto (2023)
Human activities, directly or indirectly, have made 41% of amphibian species on the planet subject to some threat of extinction. This crisis is due to the synergistic action of several factors, including the fragmentation and degradation of habitats, mainly for agricultural purposes, and exposure to contaminants derived from these activities. The ectothermic nature of amphibians and their way of life both in water and on land make them especially subject to these environmental stresses. We evaluated the effects on oxidative balance, metabolism and body condition indices due to different levels of exposure to a commercial formulation of the herbicide glyphosate (commercial formulation - Roundup®) in the species popularly known as the blacksmith tree frog (Boana faber), an anuran of the family Hylidae that occupies a large part of the Brazilian coast and is also present in almost all of the Atlantic Forest. Thus, anuran spawns were collected and, after hatching, when they reached the Gosner stage 25, they were exposed to different concentrations of glyphosate (G1: 65, G2: 260 and G3: 520 μg.L-1) for seven days. We did not observe mortality among the animals either during cultivation or during exposure to glyphosate. We performed the measurement of oxidative balance markers (superoxide dismutase, catalase, glutathione S-transferase, lipoperoxidation and carbonyl proteins), body condition factors (mass, length, K and Kn factor), a non-enzymatic antioxidant (uric acid) and metabolic markers (total proteins and total animal glycogen). Although the animals showed increased superoxide dismutase activity in the higher exposure group and maintained catalase and glutathione S-transferase activity, they were unable to contain the levels of carbonylation of their proteins, demonstrating oxidation of the same and, thus, suffering oxidative stress. The measured indices of body condition did not reveal significant differences in the length, mass, K and Kn factor of the exposed animals. However, at the highest herbicide concentration, all these indices showed a value lower than the exposure control. These results, combined with the intense reduction of glycogen levels in all exposed concentrations, indicate the use of this polysaccharide for animal survival. The set of biomarkers analyzed showed that this herbicide can cause alterations in the antioxidant defenses, in the metabolism and, consequently, in the body condition parameters of tadpoles, which can compromise the development time of the species and, possibly, its fitness